The Effect of Melatonin and Exercise on Social Isolation-Related Behavioral Changes in Aged Rats - Alghamdi, Badrah Saeed (Frontiers in Aging Neuroscience, 2022)
Social isolation (SI) is well established as an environmental factor that negatively influences different behavioral parameters, including cognitive function, anxiety, and social interaction, depending on the age of isolation. Aging is a physiological process that is associated with changes in cognitive function, locomotor activity, anxiety and emotional responses. Few studies have investigated the effect of SI in senescence, or possible interventions. In the current study, we investigated the possible complementary effects of melatonin (MLT) and exercise (Ex) in improving SI-related behavioral changes in aged rats. Forty aged Wistar rats (24 months old) were randomly divided into five groups (n = 8 per group): Control (group housing), SI (individual housing for 7 weeks), SI + MLT (SI rats treated with 0.4 mg MLT/ml in drinking water), SI + Ex (SI rats treated with 60 min of swimming), and SI + MLT + Ex (SI rats treated with both MLT and Ex). Different behavioral tasks were conducted in the following sequence: open field test, elevated plus maze test, sucrose preference test, Y maze test, and Morris water maze test. Locomotor activities measured by total distance moved and velocity revealed that SI + Ex (P = 0.0038; P = 0.0015) and SI + MLT + Ex (P = 0.0001; P = 0.0003) significantly improved the locomotor activity compared with SI rats but SI + MLT (P = 0.0599; P = 0.0627) rats showed no significant change. Anxiety index score was significantly improved in SI + MLT + Ex (P = 0.0256) compared with SI rats while SI + MLT (P > 0.9999) and SI + Ex (P = 0.2943) rats showed no significant change. Moreover, latency to reach the platform in Morris water maze was significantly reduced at day 5 in SI + MLT + Ex (P = 0.0457) compared with SI rats but no change was detected in SI + MLT (P = 0.7314) or SI + Ex (P = 0.1676) groups. In conclusion, this study supports the possible potential of MLT in combination with Ex in improving physical activity, anxiety, and cognitive functions in aging population.